Dynamic Meta-data Network Sparse PCA for Cancer Subtype Biomarker Screening - Miao, Rui; Dong, Xin; Liu, Xiao-Ying; Lo, Sio-Long; Mei, Xin-Yue; Dang, Qi; Cai, Jie; Li, Shao; Yang, Kuo; Xie, Sheng-Li; Liang, Yong (Frontiers in Genetics, 2022)
Previous research shows that each type of cancer can be divided into multiple subtypes, which is one of the key reasons that make cancer difficult to cure. Under these circumstances, finding a new target gene of cancer subtypes has great significance on developing new anti-cancer drugs and personalized treatment. Due to the gene expression data sets of cancer are usually high dimensional, high noise, and have multiple potential subtypes information, many sparse principal component analysis (sparse PCA) methods have been used to identify cancer subtype biomarkers and subtype clusters. However, the existing sparse PCA methods have not used the known cancer subtype information as prior knowledge and their results are greatly affected by the quality of the samples. Therefore, we propose Dynamic Metadata Edge-group Sparse PCA (DM-ESPCA) model which combines with the idea of meta-learning to solve the problem of sample quality and uses the known cancer subtype information as prior knowledge to capture some gene modules with better biological interpretations. The experiment results on the three biological data sets showed that the DM-ESPCA model can find potential target gene probes with richer biological information to the cancer subtypes. Moreover, the results of clustering and machine learning classification models based on the target genes screened by the DM-ESPCA model can be improved by up to 22-23% of accuracies compared with existing sparse PCA methods. We also proved that the result of DM-ESPCA model is better than the four classic supervised machine learning models in the task of classification of cancer subtypes.